Control of a Multilevel Inverter for Wind Energy Conversion System with Energy Storage and Condition Monitoring Options - Hossain, Md. Liton (Curtin University, 2020)
A generalized three-phase cascaded multilevel inverter (CMLI) is proposed which requires four non-isolated series-connected dc-link capacitors only. A simplified space vector pulse width modulation (SVPWM) controller is proposed to control the three-phase CMLI, to balance and minimize the ripples of dc-link voltages. In addition, algorithms are proposed to monitor the condition of dc-link capacitors and switching devices in real-time remotely over internet. Three-phase CMLI, simplified SVPWM, and algorithms have been tested through simulation and experiment.